The Effectiveness of Restraining Orders as a Tool for Preventing and Countering Domestic Violence - N. O. Hrom (Bulletin of Kharkiv National University of Internal Affairs)
The article provides a comprehensive analysis of the effectiveness of a special measure to combat domestic violence – an emergency restraining order – as a key tool in the system of preventing and combating domestic violence. It examines its specific features, which consist of its rapid application, prevention of harm to the mental and physical health of the victim, and the ability to immediately isolate the abuser from the victim without lengthy bureaucratic procedures. Particular attention is paid to the role of risk assessment at the stage of issuing an emergency restraining order, the challenges faced by law enforcement agencies, including mistrust on the part of judges. It has been found that, despite the potential of this institution, judicial practice often demonstrates distrust of police decisions to issue emergency restraining orders based on risk assessment and personal conviction, which ultimately negates the key advantages of the order, such as speed and effectiveness. The article also examines the complex issue of the violation of the constitutional rights of abusers in the case of issuing an emergency restraining order against them, which, although aimed at protecting the victim, nevertheless temporarily restricts certain rights of the person suspected of domestic violence. In conclusion, the properties of an emergency restraining order are outlined, including the following: a tendency to regulate in detail the procedural aspects of issuing an emergency restraining order and bringing administrative liability for its violation, related to the ratification of the provisions of the Istanbul Convention; the fact that this procedure is carried out exclusively by competent employees of the National Police of Ukraine; the impossibility of issuing an urgent restraining order without carrying out another procedure – conducting a risk assessment of domestic violence; mandatory documentation, the rules and forms of which are established by current administrative legislation; the purpose of this administrative procedure is to immediately stop domestic violence and prevent its continuation; the efficiency and effectiveness of this measure.